(untitled) (Journal of Health, Technology and Science (JHTS), 2025)
This study aims to examine the application of excipient co-processing technology based on microcrystalline cellulose (MCC) and hydroxypropyl methylcellulose (HPMC) in the formulation of sambiloto extract tablets. Sambiloto extract which is rich in active compounds andrographolide has the potential as an immunomodulator and antiviral, but the physicochemical characteristics of the extract which are hygroscopic, incompressible, and difficult to flow cause challenges in the tablet formulation process. Co-processing technology is expected to improve the flow properties of the powder, compressibility, and dissolution rate of the tablet. The study was conducted experimentally by making five tablet formulas (F1–F5) using variations in the composition of co-processed excipients. Evaluation of parameters such as angle of repose, carr index , hardness, friability, disintegration time, and dissolution rate showed that the higher the content of co-processed excipients, the better the quality of the tablets. Formula F4 (MCC:HPMC 70:30) gave the best result with angle of repose of 29.5°, carr index of 13.8%, hardness of 6.3 kg/cm², friability of 0.4%, disintegration time of 18 minutes, and dissolution rate of 89% in 60 minutes. This result meets the standard of Indonesian Pharmacopoeia and BPOM RI requirements. Thus, the excipient co-processing technology has proven to be effective in improving the technological properties of sambiloto extract tablets and is feasible to be applied in industrial scale production.